The principle of the reversal of the burden of proof in anti-discrimination cases in the context of the Court of Justice of the European Union C-81/12 and C-415/10 - Tyc, Aneta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The author of the article refers to two judgements of the Court of Justice of the European Union, which relate to the principle of the reversal of the burden of proof in anti-discrimination cases. She focuses on the facts, from which it may be presumed that there has been discrimination. It cannot be ruled out that a defendant’s refusal to grant any access to information may be one of the factors to take into account in the context of establishing facts from which it may be presumed that there has been direct or indirect discrimination (C-415/10). Public statements ruling out the recruitment of a footballer presented as being homosexual are considered to be “the facts from which it may be presumed that there has been discrimination, even though they come from a person presenting himself and being perceived in the media and among the general public as playing a leading role in that club without, however, necessarily having legal capacity to bind it or to represent it in recruitment matters (C-81/12).